Morphology-controlled approach for bulk synthesis of conducting poly (5-aminoindole) - Mishra R.; Gupta S.; Kumar A.; Prakash R. (My University, 2025)
Interfacial synthesis is an excellent controlled approach to obtain polymer at the interface of two immiscible solvents without aid of any phase transfer agent. We report here, bulk and morphology controlled synthesis of poly (5-aminoindole), 5-APIn conducting polymer at the liquid/liquid interface exhibiting 1, 3-linkages. 5-APIn displays uniqueness in redox behavior (in comparison to other polyindole family) i.e. p-type as well as n-type doped property on application of positive and negative voltages (cyclic voltammetry) in non-aqueous medium. This exclusive behavior is due to amine moiety on polymer backbone. At the same time, 5-APIn is electroactive at acidic pH, inferred from the redox quasi-reversibility (due to protonation of amino group) at lower potential between two well-proposed states. Time-dependent polymerization progress of 5-AIn at interface is monitored via SEM that reveals its porous texture that facilitated electron transfer over polymer matrix (ascertained by EIS). To estimate the judicious structure and electronic properties of the as-synthesized polymer, experimental and computational efforts are done. The optical band gap (Eg) obtained via UV-vis spectroscopy is 3.06 eV and band gap (Ecv) from CV (non-aqueous medium) is found to be 3.07 eV. Density functional theory (DFT) calculations using range-separated hybrid functional predicted the electronic band gap, ΔE (3.82 eV) of 5-APIn, which agree reasonably well with the experimental data. © 2016 Elsevier B.V.